Aplicação dos direitos fundamentais de 1ª dimensão nas relações jurídicas privadas - Santos, Lucas Sampaio (2012)
The purpose of this study is to present a systematization of legal thought on the horizontal effectiveness of the fundamental rights listed in the Brazilian Constitution of 1988; in other words, in order to better understand whether these rights may be applied in private legal relations, and, if so, how will such rights be applied in said relations. This issue has become increasingly significant because of the verification that not only the State is capable of violating said fundamental rights, but also that, in many cases, private entities such as multinational companies, banks, unions, etc., are the agents involved in said violations. As such, this study analyzes how and through which means is it possible to sustain the horizontal efficiency of fundamental rights based on the Brazilian legal system currently in effect. Both national and foreign doctrine and jurisprudence were assessed in order to do so. The assessment of the text reveals that our intention is to provide a model for the application of such rights in private relations, especially with respect to first dimension of fundamental rights, thereby specifying how and in which way private parties are bound to said rights, and also to establish intersubjectively verifiable parameters to apply the rights in relations between private parties. The conclusion to the study includes certain considerations on the need to acknowledge said bind, in addition to the need to structure a model to favor the application of fundamental rights in relations between private parties